Epistemologi Penafsiran Farid Esack terhadap Ayat-Ayat Pembebasan - Kamaruddin Mustamin; Basri Basri (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2020)
This article discusses Farid Esack 's epistemological side, who proposed an emancipatory interpretation of what was generally known as liberation hermeneutics in responding to social problems in South Africa. The method used in this research is the library method with analytical material and a historical-philosophical approach that functions to (a) analyze the text itself; (b) objectively trace the historical origins of the character's context, why it carried the hermeneutic idea of its liberation; and (c) analyze the socio-historical circumstances surrounding the character and find the essential building. Based on the research result, the researcher found that Farid Esack 's thought-building was highly motivated by South Africa's socio-historical circumstances enduring humanitarian problems (apartheid). Farid Esack used critical reasoning (al-aql al-naqdy) in which the role of revelation (text), truth (context), and interpreter (reader) was linked in the compilation of his tafsir book. Meanwhile, the method of interpretation was the hermeneutics of the Qur'an based on the context and life experiences of the South African people, whose results were intended as the philosophical basis for freeing the whole society from all types of inequality and exploitation of economy, race, gender, class, and religion.